(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the history and source studies of the role and significance of Islam in the socio-political and spiritual life of Turkestan in the late 19th and early 20th centuries. The works of Russian authors on the study of the state of Islam in Turkestan are analyzed in detail. Furthermore, the archival documents kept in the funds of the Academy of Sciences of the Republic of Uzbekistan and articles published by national intellectuals and scholars-theologists in local newspapers and magazines in the late 19th and early 20th centuries were studied.